Investigation of RelBE1 toxin-antitoxin function in the carbon-dependent metabolic adaptation of Mycobacterium tuberculosis - Starkey, Julie M., author; Slayden, Richard, advisor; Dobos, Karen, committee member; Abdo, Zaid, committee member; Tjalkens, Ron, committee member (Colorado State University. Libraries, 2022)
Tuberculosis (TB) is a devastating disease with suboptimal treatment regimens and a single vaccine with variable efficacy. Reducing the global burden of TB requires a refined arsenal of methods to prevent and treat the disease, which necessitates a better understanding of M. tuberculosis (Mtb) pathogenesis during infection. Mtb undergoes continuous metabolic reprogramming throughout acute and chronic stages of infection in order to survive and persist harsh host conditions, and the regulatory network responsible for mediating metabolic adaptation has not been fully defined. Mtb harbors at least 88 Toxin-antitoxin (TA) loci that have been proposed to function as regulatory modules in response to stress. TA systems are uniquely abundant in Mtb, making them viable targets for the treatment of both active and latent infection. Several RelBE TA systems are present in Mtb, and the RelE toxins function as ribonucleases to inhibit translation when not bound to RelB antitoxins. The genes encoding relBE1 are adjacent to a gene that encodes an enzyme involved in central carbon metabolism, which could suggest a regulatory role for RelBE1 in carbon metabolism. We aimed to explore the relationship between the RelBE1 TA system and carbon-mediated metabolic adaptation. This work incorporated in vitro transcriptional and genetic studies under defined carbon sources to investigate the activity of RelBE1 and the requirement of RelE1 in Mtb metabolism, growth, and viability in the presence of different carbon sources. We observed transcriptional and physiological trends consistent with the hypothesis that RelBE1 contributes to iii adaptation of Mtb metabolism in the presence of cholesterol and oleate. Additionally, we found evidence that supports the necessity of RelE1 in Mtb metabolism under conditions depleted of nutrients. To investigate if multiple RelBE systems work redundantly or cooperatively in Mtb metabolic adaptation, we applied CRISPRi to simultaneously silence three RelBE TA loci. CRISPRi construction of knockdown mutants resulted in variable success but did not fully resolve the question regarding the cooperative or redundant functions of RelBE systems in Mtb metabolism. Nonetheless, the study provided the building blocks for efficient genetic manipulation of multiple TA systems in Mtb that are essential for exploring the coordination of TA systems in their contribution to Mtb pathogenesis. This thesis work contributes to the debate regarding TA system function in Mtb stress response and adaptation during infection. Given the limitations of the presented studies, further work is warranted to elucidate the relationship between TA systems and Mtb pathogenesis. Expanding our understanding of TA systems in TB disease would provide novel avenues in research to improve treatments against TB.
Keywords: carbon sources; Mtb; tuberculosis; metabolism; adaptation; toxin-antitoxin systems